2014
DOI: 10.1111/bjet.12222
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to blended digital distance vocational learning for non‐traditional students

Abstract: This research identifies and examines the challenges of blending digital distance and vocational learning for non‐traditional and low‐socio‐economic status students who are new to university education. A survey of students in vocational primary education and early years qualifications in a distance university is illuminated by interviews with individual students and video diaries recorded by them during module study. Barriers to study include where and when to go online, finding support for digital study, navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 14 publications
1
53
0
6
Order By: Relevance
“…international postgraduate students (Coates & Dickinson, 2012); those transitioning to university (Harnisch & Taylor-Murison, 2012); students studying foreign languages (O'Dowd, 2013); non-traditional students (Safford & Stinton, 2016); and pre-service teachers (Keengwe & Kang, 2013). Generally however, research that focussed specifically on demographics (3.9%, n=6) was limited, featuring articles relating to, for example, students with disabilities (Heiman, Fichten, Olenik-Shemesh, Keshet, & Jorgensen, 2017); and student characteristics and their achievement on blended courses (Gašević et al, 2016).…”
Section: Approach Percentmentioning
confidence: 99%
“…international postgraduate students (Coates & Dickinson, 2012); those transitioning to university (Harnisch & Taylor-Murison, 2012); students studying foreign languages (O'Dowd, 2013); non-traditional students (Safford & Stinton, 2016); and pre-service teachers (Keengwe & Kang, 2013). Generally however, research that focussed specifically on demographics (3.9%, n=6) was limited, featuring articles relating to, for example, students with disabilities (Heiman, Fichten, Olenik-Shemesh, Keshet, & Jorgensen, 2017); and student characteristics and their achievement on blended courses (Gašević et al, 2016).…”
Section: Approach Percentmentioning
confidence: 99%
“…It is anticipated that continued research on how higher education students attribute and respond emotionally to academic technology challenges will serve to inform future educational technology development, classroom instructional support, IT support services, and intervention efforts (e.g., attributional retraining; Hall et al 2004Hall et al , 2007, and provide a useful framework for applying Weiner's (2010) attribution theory to understanding how technological challenges are experienced in other academic settings (e.g., students in asynchronous online learning environments, secondary and post-secondary instructors). For example, further research examining attributions and emotions following technological problems could help students in online distance education programs in light of research showing online students to have overall higher emotion ratings compared to traditional students (e.g., anger, anxiety, helplessness; Butz et al 2015) and to consistently identify technological difficulties as a source of frustration or stress (Hara 2000), with some citing "computer problems" specifically in qualitative studies (Safford and Stinton 2016). More recent research has also found significant relationships between attributions and emotions following computer problems to differ between traditional and online students (Maymon et al 2018), highlighting the relevance of attribution theory in examining motivational processes following technological difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…ICT in the form of e-learning media is a technological tool to assist, and facilitate communication, delivery and processing of information through electronic means [12]. [13] It states that distance learning (e-learning) can enhance and precipitate knowledge and provide broad access to increase students' participation. Harandi's [14] findings show that when teachers implement e-learning, the students' motivation will improve.…”
Section: Blended Learningmentioning
confidence: 99%